2009
DOI: 10.2174/1874210600903010074
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Surface-Enhanced Laser Desorption/Ionization Time-Of-Flight (SELDI-TOF) Mass Spectrometry in Defining Salivary Proteomic Profiles

Abstract: Recent advancement in mass spectrometry leads us to a new era of proteomic analysis. Human saliva can be easily collected; however, the complexity of the salivary proteome in the past prevented the use of saliva for proteomic analysis. Here we review the development of proteomic analyses for human saliva and focus on the use of a new mass spectrometric technology known as surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF). SELDI-TOF, a modification of matrix-assisted lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…1922 It was important to note here that this proteomic profiling corresponds well with clinical and histological diagnosis of DS. More importantly, each protein is differentially expressed among the non-DS, DS II and DS III individuals.…”
Section: Discussionsupporting
confidence: 59%
“…1922 It was important to note here that this proteomic profiling corresponds well with clinical and histological diagnosis of DS. More importantly, each protein is differentially expressed among the non-DS, DS II and DS III individuals.…”
Section: Discussionsupporting
confidence: 59%
“…These proteases potentially degrade protein biomarkers. It has been shown that leaving saliva samples for a period of time can alter proteomic profiles and change the biomarker content (Al-Tarawneh and Bencharit, 2009). Shortening the time of storage before centrifugation, fast frozen (with dried ice or liquid nitrogen), storing the samples in low temperature (À808C), and avoiding multiple freeze-thaw processes, as well as consistent sample collection protocol, are known to enhance consistent proteomic analytical results and the degradation of sensitive protein biomarkers (Schipper et al, 2007).…”
Section: Saliva Collection and Handling Processmentioning
confidence: 99%
“…This technique was used in some studies for initial profiling prior to further identification using LC-MS techniques, whereas in other studies it has been used as the main identification technique after initial profiling with 2DE (Supplementary Table 2). In some cases the SELDI-TOF/MS technique where the sample matrix (Protein Chip) has an active role in sample purification, desorption/ionization, and protein separation] was used to quantify and reproduce results (Al-Tarawneh and Bencharit, 2009). …”
Section: Proteomic Techniquesmentioning
confidence: 99%
“…The use of surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry (MS), which allows rapid, high-throughput detection of proteins in minute sample volumes without pre-processing, has been reported for several diseases [58]. Recently, analysis of saliva for protein biomarker discovery has mainly been performed using two-dimensional difference gel electrophoresis (2D-DIGE) coupled with MS (which can identify around 300 proteins in a sample [59]), and liquid chromatograpy-MS (LC-MS) based techniques (which can identify more than 1,050 proteins in a sample; reviewed in [60]).…”
Section: The Salivary Proteomementioning
confidence: 99%